(untitled) (REVISTA NODO, 2021)
Tacet is the term used in musical notation to indicate a prolonged silence. This article refers to the repercussion of John Cage’s work 4’33” on the evolution of contemporary art. From this seminal work of sound art, a series of fundamental works of 20th century art have a common link in silence. The main objective is to provide a new vision of silence as a fundamental contribution of sound art, establishing the correlations and coincidences of the concept of silence in various cultural contexts. Currently, since the extreme confinement of 99 days due to the coronavirus pandemic, society has become aware of silence as a value to preserve and cultivate. As of 2020, multiple artistic proposals are being produced where the center of interest is silent action, some of which we reference in this text. The relationships established in the article contextualize the sound work Los silencios de China, an original work made by the author for Nodo magazine, the result of six years of field work in various regions of China, in which silences were recorded in various natural and urban environments. A summary of these records are the 18 recordings that are attached to the article as conclusions.